Efikasi Misa Online sebagai Sakramen Keselamatan pada Masa Pandemi Covid-19: Kritik Naratif Markus 5:25-34 - R.F. Bhanu Viktorahadi; Busro Busro (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2021)
Abstract. The emergency situation due to the Covid-19 pandemic has forced Catholics to worship by attending online mass. Although it is seen as a quick and responsive solution for the Church, many have questioned the efficacy or usefulness of online mass as a means and sign of God's salvation for His people. This paper provides an explanation of the efficacy of online mass as a sacrament of salvation by using the text Mark 5:25-34 about a haemorrhaging woman suffering who received miracles of healing after touching the garment of Jesus. This study was conducted by Narrative Criticism with the Exegetical Symbol Analysis approach. The analogy of the miracle of healing obtained by touching the robe of Jesus provides an understanding that the efficacy of online mass as a sacrament of salvation continues to work even though it is not experienced directly or in distance.Abstrak. Kondisi darurat akibat pandemi Covid-19 memaksa umat Katolik beribadah dengan mengikuti misa secara online. Walaupun dipandang sebagai solusi cepat dan tanggap Gereja, banyak yang mempertanyakan efikasi atau daya guna misa online sebagai sarana dan tanda keselamatan Tuhan bagi umat-Nya. Tulisan ini memberi penjelasan tentang efikasi misa online sebagai sakramen keselamatan dengan menggunakan teks Markus 5:25-34 tentang perempuan penderita pendarahan yang memeroleh mukjizat penyembuhan setelah menyentuh jubah Yesus. Metode yang digunakan adalah Kritik Naratif dengan pendekatan Eksegese Analisis Simbol. Analogi mukjizat penyembuhan yang diperoleh hanya dengan menjamah jubah Yesus memberikan pemahaman bahwa efikasi misa online sebagai sakramen keselamatan tetap bekerja walaupun tidak dialami secara langsung alias berjarak.